A study on split diesel injection on thermal efficiency and emissions of an ammonia/diesel dual-fuel engine. (15th May 2022) - Yousefi, Amin; Guo, Hongsheng; Dev, Shouvik; Lafrance, Simon; Liko, Brian
Highlights: Effect of split diesel injection on ADDF engine was investigated at medium load. Split injection reduced NH3 emissions by 83.5% compared to single injection. Split injection decreased GHG emission of ADDF mode by 23.7% compared to diesel mode. Split injection increased ITE of ADDF model by 2% compared to diesel mode. Abstract: Ammonia is gaining more interest as a carbon-free alternative fuel in freight transportation applications, especially the shipping industry. However, the problems of nitrous oxide (N2 O) emissions, which has almost 300 times higher global warming impact than carbon dioxide (CO2 ), and ammonia slip have been the main challenges of using ammonia in compression ignition (CI) diesel engines. In this study, the effect of split diesel injection strategy (i.e., two-pulse diesel injection) on an ammonia/diesel dual-fuel (ADDF) engine is investigated under medium load operating conditions. Results indicate that the ADDF combustion mode with single diesel injection strategy achieves lower indicated thermal efficiency (ITE) compared to the corresponding diesel-only combustion mode. However, the use of split diesel injection strategy increases the ITE of the ADDF combustion mode to 39.72% which is higher than that obtained by diesel-only combustion mode (maximum ITEdiesel = 38.62%). Moreover, split diesel injection strategy reduces the unburned ammonia emissions of the ADDF combustion mode by up to 83.5% compared to the lowest unburned ammonia emissions achieved by single diesel injection strategy. Two split diesel injection strategies based on the optimum points of greenhouse gas (GHG) emissions are suggested in this research. At the first optimum point, the GHG emissions of the ADDF combustion mode are decreased by 23.7%, while ITE is increased by about 2% compared to the optimum point of diesel-only combustion mode. This, however, comes with about 10% higher nitrogen oxides (NOx ) emissions. The emitted GHG emissions of ADDF combustion can be further reduced by 30.6%, but at the expense of 2.2% lower ITE and 52.4% higher NOx emissions than diesel-only combustion mode. At both optimum points, unburned ammonia emissions were significantly reduced to below 900 ppm compared to that of ADDF combustion mode with single diesel injection strategy (i.e., 4445 ppm). The lowest unburned ammonia concentration achieved in this study is still above the recommended exposure limit and therefore the use of appropriate after-treatment devices should be considered in the future.